Two tales of the Design Thinking Process for the Sustainable Energy Canadian Engineering Grand Challenge - Moresoli, Christine; Mikhail, Monika (Proceedings of the Canadian Engineering Education Association (CEEA), 2022)
Student awareness of complex problems increased by collaborating in teams through curricular and co-curricular deliveries. Pedagogical partnerships between faculty and students were created to investigate the Canadian Engineering Grand Challenge (CEGC), access to affordable, reliable, and sustainable energy. The open-ended and broad nature of the CEGC represented a natural fit for the design thinking process (DTP) framework where users and their needs are identified, and the problem statement and specification are formulated. The difficulties encountered by students while navigating the complex nature of the CEGC will be reported and steps for success are identified.